1972
DOI: 10.1037/h0033397
|View full text |Cite
|
Sign up to set email alerts
|

Internal-external control as situational variable in determining information seeking by Negro students.

Abstract: Negro 5s, reported to hold an external locus of control and to be relatively nonachievement-oriented, were told that they were engaged in a diadic experiment aimed either at changing attitudes or at "interaction." The Ss were randomly assigned to three groups with different levels of success expectancy and task reinforcement value. Number of questions asked about the experiment and the time spent examining each of three classes of magazine articles were used as measures of information-seeking behavior. Data su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Environmental interventions should therefore be designed in ways which encourage people to believe that they have control not just over those everyday behaviours which are environmentally significant, but over life in general. Some studies propose that cognitive training can make people more internal in their perceptions of control; for example, a cognitive training program, designed to target reasoning and speed of processing, improved the internal loci of control amongst participants (Wollinsky et al, 2010). In another cognitive training programme, participants were encouraged to believe that the achievements of positive goals were due to their own actions, and this led to more internal loci of control amongst females (Manger, Eikeland and Asbjornsen, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental interventions should therefore be designed in ways which encourage people to believe that they have control not just over those everyday behaviours which are environmentally significant, but over life in general. Some studies propose that cognitive training can make people more internal in their perceptions of control; for example, a cognitive training program, designed to target reasoning and speed of processing, improved the internal loci of control amongst participants (Wollinsky et al, 2010). In another cognitive training programme, participants were encouraged to believe that the achievements of positive goals were due to their own actions, and this led to more internal loci of control amongst females (Manger, Eikeland and Asbjornsen, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…People who attribute control to themselves tend to seek and acquire information which they consider useful for controlling their environment or achieving their personal goals more efficiently than those who attribute it to external sources (Davis and Phares, 1967;DuCette and Wolk, 1973;Phares, 1968;Prociuk and Breen, 1977;Seeman and Evans, 1962;Williams and Stack, 1972). Amongst people who value the environment and feel the need to protect nature, it can be assumed that those with an internal locus of control more actively seek out information about environmental problems; as a result, they acquire more often, and make better use of, knowledge which helps towards behaving in an environmentally-friendly manner.…”
Section: Locus Of Controlmentioning
confidence: 99%
“…Specifically, it was hypothesized that teacher preferences for consultation versus referral services would vary as a function of how much personal control teachers perceived they had in regard to presenting problems. Prior work in the area of locus of control has shown that subjects who feel they can have an impact on the rewards and punishments they receive (i.e., internals) are more likely than those who do not feel as such (i.e., externals) to actively seek out and utilize information when confronted with problems (Davis & Phares, 1967;Phares, 1968;Seeman, 1963Seeman, ,1967Williams & Stack, 1972). Numerous authors (e.g., Gutkin & Curtis, 1982) have theorized that school-based consultation provides teachers with substantially more opportunities to be actively involved in the generation of assessment, diagnosis, and treatment plans than do traditional referral approaches.…”
Section: Teachers 9 Perceptions Of Control and Preferences For Consul...mentioning
confidence: 99%
“…Black subjects have been shown to seek more information (William & Stack, 1972) and to persist longer in performance (Lefcourt & Ladwig, 1965) at tasks characterized by high interest value. Williams and Stack (1972) presented black college students with the task of preparing a persuasive statement to be delivered to another subject on one of two topics: "The contributions made by black individuals to society;" or, "the role of the U.S. Vice President in national and foreign affairs." The former task was conceived as having high interest-value, while the latter was conceived of as low in interest-value for the subject population.…”
Section: Relevant Researchmentioning
confidence: 99%